Discovery of DC_H31 as potential mutant IDH1 inhibitor through NADPH-based high throughput screening. Issue 15 (1st August 2019) - Duan, Zhe; Liu, Jingqiu; Niu, Liping; Wang, Jun; Feng, Mingqian; Chen, Hua; Luo, Cheng
Graphical abstract: Abstract: IDH1 mutations are early events in the development of IDH-mutant gliomas and leukemias and are associated with various regulation of molecular process. Mutations of active site in IDH1 could lead to high levels of 2-HG and the suppression of cellular differentiation, while these changes can be reversed by molecule inhibitors target mutant IDH1. Here, through in-house developed enzymatic assay-based high throughput screening platform, we discovered DC_H31 as a novel IDH1-R132H/C inhibitor, with the IC50 value of 0.41 μmol/L and 2.7 μmol/L respectively. In addition, saturable SPR binding assay indicated that DC_H31 bound to IDH1-R132H/C due to specific interaction. Further computational docking studies and structure-activity relationship (SAR) suggest that DC_H31 could occupy the allosteric pocket between the two monomers of IDH1-R132H homodimer, which accounts for its inhibitory ability. And it is possible to conclude that DC_H31 acts via an allosteric mechanism of inhibition. At the cellular level, DC_H31 could inhibit cell proliferation, promote cell differentiation and reduce the production of 2-HG with a dose-dependent manner in HT1080 cells. Taken together, DC_H31 is a potent selective inhibitor of IDH1-R132H/C both in vitro and in vivo, which can promote the development of more potent pan-inhibitors against IDH1-R132H/C through further structural decoration and provide a new insight for the pharmacological treatment of gliomas.